Cyclophosphamide Induces the Ferroptosis of Tumor Cells Through Heme Oxygenase-1 - Shi, Hezhan; Hou, Bo; Li, Huifeng; Zhou, Hui; Du, Bin (Frontiers in Pharmacology, 2022)
Ferroptosis has been implicated in the therapeutic responses of various types of tumors. Cyclophosphamide (CTX), one of the most successful antitumor agents, is widely used to treat both hematopoietic and solid tumors. In this study, we revealed the ferroptosis pathway targeted by CTX treatment in tumor cells and clarified its mechanisms. Cell viability was remarkably suppressed by CTX, accompanied by the accumulation of intracellular iron and reactive oxygen species, reduced glutathione levels, deformed mitochondria and a loss of the mitochondrial membrane potential. These effects were impeded by the ferroptosis inhibitors ferrostatin-1 (Fer1) and deferoxamine (DFO). Moreover, CTX treatment obviously upregulated nuclear factor E2 related factor 2 (NRF2) and heme oxygenase-1 (HMOX-1) expression. Additionally, the HMOX-1 inducer Hemin notably enhanced CTX-mediated tumor inhibition in vitro and in vivo through a mechanism that involved interfering with the ferroptosis process. Therefore, our findings indicated ferroptosis induction by CTX through the activation of the NRF2/HMOX-1 pathway, which might provide a potential strategy for tumor chemotherapy.